Concurrent radiochemotherapy in advanced hypopharyngeal cancer - Krstevska, Valentina; Stojkovski, Igor; Lukarski, Dusko (My University, 2010)
Concurrent platinum-based radiochemotherapy has been recommended as a standard of care in patients with locally advanced squamous cell head and neck carcinomas. Unfortunately, there is a lack of level one evidence on best treatment approach for advanced hypopharyngeal cancer. This report aims to summarize the results of our study on concurrent radiochemotherapy in patients with advanced hypopharyngeal cancer.
Keywords: Advanced Hypopharyngeal Cancer; Concurrent Radiochemotherapy